Predictive Parameters of Steroid Dependency in Minimal Change Disease - Esra Nagehan Akyol Önder; Pelin Ertan (Galenos Publishing House, 2022)
The most common type of nephrotic syndrome in children is minimal change disease (MCD), which is usually responsive to steroid therapy. Steroid dependency is one of the handicaps in the management of these children. Thus, the early prediction of the disease course may improve treatment strategy. Demographic characteristics and laboratory parameters of 35 patients at the time of MCD diagnosis were retrospectively obtained from the hospital records. There were 23 (65%) patients with steroid sensitive (SSNS) and 12 (35%) with steroid dependent nephrotic syndrome (SDNS). There was a significant difference between the patients with SSNS and SDNS in terms of age at diagnosis, remission time, and mean values of platelet volume, low density lipoprotein cholesterol, uric acid, urine protein-to-creatinine ratio, total cholesterol and creatinine (p = 0.003, p < 0.001, p = 0.013, p = 0.006, p = 0.036, p = 0.02, p = 0.003, and p = 0.034, respectively). The prediction of early markers of steroid dependency can reduce the side effects of steroids and facilitate the use of appropriate drugs.